2008
DOI: 10.4049/jimmunol.181.12.8199
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Thymic Crosstalk Regulates Delta-Like 4 Expression on Cortical Epithelial Cells

Abstract: Interactions between Notch1 receptors on lymphoid progenitors and Delta-like 4 (DL4) ligands on cortical thymic epithelial cells (cTEC) are essential for T cell lineage commitment, expansion, and maturation in the thymus. Using a novel mAb against DL4, we show that DL4 levels on cTEC are very high in the fetal and neonatal thymus when thymocyte expansion is maximal but decrease dramatically in the adult when steady-state homeostasis is attained. Analysis of mutant mouse strains where thymocyte development is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 22 publications
9
57
1
Order By: Relevance
“…A heterogeneity within the cortical microenvironment is suggested to exist on the basis of the differential expression of CD205, Ly51, IL-7, Dll4, b5t, and CCRL1 (17,18,22,26,34,35). Our kinetic analysis during thymic ontogeny revealed that Il7…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A heterogeneity within the cortical microenvironment is suggested to exist on the basis of the differential expression of CD205, Ly51, IL-7, Dll4, b5t, and CCRL1 (17,18,22,26,34,35). Our kinetic analysis during thymic ontogeny revealed that Il7…”
Section: Discussionmentioning
confidence: 91%
“…These findings have raised the hypothesis that lymphoepithelial interactions affect the size and function of cortical epithelial microenvironments while promoting mTEC diversification (17)(18)(19) (20) and Marilyn-Rag2 2/2 (21) C57BL/6 background. Dual reporter mice were generated by crossing IL-7 reporter mice with Ccrl1: eGFP reporter mice (CCRL1-reporter) (22).…”
Section: Il2rgmentioning
confidence: 99%
“…10,11,29,47 Data from several reports support the notion that thymocytes supply "crosstalk" signals to support TEC development in both mice and humans. [48][49][50][51][52][53] This idea may also hold true for TEC regeneration after depletive regimens. Additive restoration of TECs by 4 weeks after BMT observed in KGF ϩ PFT-␤-treated BM transplant recipients may be due to PFT-␤-mediated protection combined with TEC expansion driven by mature SP thymocytederived crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…1C). The association of the expression of DLL4, specifically to the DN microenvironment, has been reported (31)(32)(33), in that the different levels of expression of Ly51 seem to distinguish between two functionally different cTEC subsets. Mutant mice showed alterations in Ly51 expression and the distribution of these cTEC subpopulations.…”
Section: Ephrin-b Expression On Both Tecs and Thymocytes Is Necessarymentioning
confidence: 99%